Exploring Leadership Styles Adopted in Organizational Performance of ADNOC Company - Alshehhi, Hamad Ali; Jano, Zanariah; Kudus, Norliah (International Journal of Sustainable Construction Engineering and Technology, 2023)
Leadership style is critical for improving organisational performance, and inappropriate leadership styles harm both employees and the overall performance of any organisation. Poor leadership is likely to be the cause of unethical practises, a high turnover rate, and employee disengagement. Furthermore, they may use an ineffective leadership style when dealing with project subordinates. Subordinate performance that is effective is always desired, but it does not always occur. As a result, the current study investigated the four leadership styles and the characteristics that influence organisational performance. The analysis of 398 questionnaire forms collected from ADNOC Company participants revealed that all the attributes of the four leadership styles used in the UAE are reliable. Transformational leadership is found to be the most influential leadership style, while democratic leadership is the least influential in influencing the organisational performance of the ADNOC Company in the UAE. In transformational leadership, leaders focus on employees’ beliefs about their jobs as the most influential attribute. Leaders in our organisation are reported to have good communication with other employees as one of the most influential attributes in Transactional leadership style. Similarly, the most influential attributes in Charismatic Leadership style are leaders in our organisation are effective in managing our organisation. The most influential attribute of Democratic leadership is that leaders in our organisation work hard with other workers. Results of this study will able to assist the company in dealing its leadership style.